PEMBUKTIAN PENIPUAN INVESTASI MATA UANG KRIPTO DALAM PIG BUTCHERING SCAM - Goldwen, Fishella; Hutabarat, Rugun Romaida (Legal Standing : Jurnal Ilmu Hukum, 2024)
Cryptocurrency investment fraud in the form of Pig Butchering Scam has emerged as a rapidly evolving type of cybercrime that is difficult to trace. This study aims to examine the scheme and the evidentiary process of Pig Butchering Scam in the context of cryptocurrency investment fraud. Utilizing a normative approach, this research analyzes legal documents and regulations related to cryptocurrency investment. Secondary data were obtained from policy analysis and academic literature. The findings of this research identify Pig Butchering fraud as a type of romance-based scam. Perpetrators deceive victims by building trust and convincing them to participate in fraudulent investments. Once the victim trusts the perpetrator and deposits personal funds, these funds are entirely siphoned off by the fraudsters, who subsequently disappear. Resolving such cases under criminal procedural law proves challenging due to the involvement of multiple complex aspects. This study recommends that the Indonesian Government urgently establish specific evidentiary regulations regarding the Pig Butchering Scam scheme in cryptocurrency investment fraud. These regulations could serve as a guideline for law enforcement in Indonesia, similar to the Anti-Telecommunications and Online Fraud Law implemented in China.